2021
DOI: 10.3390/genes12050610
|View full text |Cite
|
Sign up to set email alerts
|

Achromobacter xylosoxidans and Stenotrophomonas maltophilia: Emerging Pathogens Well-Armed for Life in the Cystic Fibrosis Patients’ Lung

Abstract: In patients with cystic fibrosis (CF), the lung is a remarkable ecological niche in which the microbiome is subjected to important selective pressures. An inexorable colonization by bacteria of both endogenous and environmental origin is observed in most patients, leading to a vicious cycle of infection–inflammation. In this context, long-term colonization together with competitive interactions among bacteria can lead to over-inflammation. While Pseudomonas aeruginosa and Staphylococcus aureus, the two pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 178 publications
(268 reference statements)
1
43
0
1
Order By: Relevance
“…Interestingly, efflux pump encoding genes were listed among those in which altered level of expression or mutations were reported as contributors to CF lung adaptation in P. aeruginosa [191], B. cenocepacia [136], Achromobacter sp. [146] and S. maltophilia [16]. This has been mainly ascribed both to their role in biofilm formation and in bacterial virulence [61], highlighting a wider role of efflux systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, efflux pump encoding genes were listed among those in which altered level of expression or mutations were reported as contributors to CF lung adaptation in P. aeruginosa [191], B. cenocepacia [136], Achromobacter sp. [146] and S. maltophilia [16]. This has been mainly ascribed both to their role in biofilm formation and in bacterial virulence [61], highlighting a wider role of efflux systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while early infections by CF pathogens can be intermittent and involve different strains with multiple levels of antibiotic resistance (AR) profiles, subsequently, people with CF are chronically colonized with well adapted strains with properties (among which high levels of MDR) that differ significantly from those exhibited by the isolate which gave rise to the infection [13,14].This change is related to the adaptation of bacteria to the fluctuating and heterogeneous conditions of the CF lung environment, which exerts a high selective pressure [15]. CF lung is indeed an ecological niche characterized by several selective elements, including the host immune response, the oxidative stresses especially derived from the liberation of reactive oxygen species (ROS) by neutrophils, the interactions among different microorganisms, the nutrient availability, the modified acidity and salinity of the surrounding environment, and the oxygen deprivation in mucus [14][15][16]. Moreover, a strong selective pressure is exerted by the high levels of antibiotics used to treat the infections caused by CF pathogens (a summary of the antibiotic treatment used for the CF pathogens described in this review is reported in Supplementary Table S1) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial populations colonizing CF patients are known to be highly complex and dynamic, encompassing a variety of variants whose equilibrium varies according to the changing conditions of the surrounding environment. This population diversification is an increasingly well-known host adaptation strategy which has been widely studied in Gram-negative bacilli during chronic colonization of CF patients' lungs (Winstanley et al, 2016;Menetrey et al, 2021). For S. aureus, diversified populations have been more rarely documented in CF (Goerke et al, 2007;Vu-Thien et al, 2010;Hirschhausen et al, 2013;Ankrum and Hall, 2017;Boudet et al, 2021;Wieneke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Achromobacter infection occurs most commonly in CF patients with advanced lung disease and is associated with a poor clinical course [2][3][4][5][6][7]. Achromobacter species are well-armed for colonisation and persistence in the CF lung, as they harbour a large panel of adaptive strategies (biofilm formation, antibiotic resistance, hypermutation, secretion and quorum sensing systems) [8]. However, the current evidence is insufficient to attribute a major role in disease progression and large prospective studies assessing the pathogenicity of this emerging pathogen are warranted.…”
Section: Introductionmentioning
confidence: 99%